2020
DOI: 10.1017/s0033291720001531
|View full text |Cite
|
Sign up to set email alerts
|

Long-term behavioural rewriting of maladaptive drinking memories via reconsolidation-update mechanisms

Abstract: Background Alcohol use disorders can be conceptualised as a learned pattern of maladaptive alcohol-consumption behaviours. The memories encoding these behaviours centrally contribute to long-term excessive alcohol consumption and are therefore an important therapeutic target. The transient period of memory instability sparked during memory reconsolidation offers a therapeutic window to directly rewrite these memories using targeted behavioural interventions. However, clinically-relevant demonstrations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Laboratory studies of more complex design indicate the ecological validity of the unlearning sequence, as noted earlier. The fact that the unlearning sequence is defined as certain subjective experiences, rather than particular procedures, has allowed it to be fulfilled in creative ways in various empirical studies of its therapeutic application: Gray et al (2017, 2020) and Iyadurai et al (2018) report the successful use of specialized protocols designed for posttraumatic stress disorder rooted in a single event, and various protocols have been developed and applied for particular addictions (e.g., alcohol addiction: Gale et al, 2021; cocaine seeking: Luo et al, 2015; heroin craving: Xue et al, 2012; nicotine addiction: Germeroth et al, 2017; internet gaming addiction: Zhao et al, 2022). The protocol developed by Högberg et al (2011) for suicidal adolescents eliminated their posttraumatic symptomology in a small number of therapy sessions, and an analysis of that protocol by Ecker (2018, pp.…”
Section: The Core Change Universe: Memory Change Via Mrmentioning
confidence: 99%
“…Laboratory studies of more complex design indicate the ecological validity of the unlearning sequence, as noted earlier. The fact that the unlearning sequence is defined as certain subjective experiences, rather than particular procedures, has allowed it to be fulfilled in creative ways in various empirical studies of its therapeutic application: Gray et al (2017, 2020) and Iyadurai et al (2018) report the successful use of specialized protocols designed for posttraumatic stress disorder rooted in a single event, and various protocols have been developed and applied for particular addictions (e.g., alcohol addiction: Gale et al, 2021; cocaine seeking: Luo et al, 2015; heroin craving: Xue et al, 2012; nicotine addiction: Germeroth et al, 2017; internet gaming addiction: Zhao et al, 2022). The protocol developed by Högberg et al (2011) for suicidal adolescents eliminated their posttraumatic symptomology in a small number of therapy sessions, and an analysis of that protocol by Ecker (2018, pp.…”
Section: The Core Change Universe: Memory Change Via Mrmentioning
confidence: 99%
“…Interference with memory reconsolidation by post-retrieval counterconditioning has also been successfully tested in humans [ 56 ], showing particularly promising results in modulating craving and drinking patterns in hazardous alcohol drinkers [ 54 , 74 , 75 ]. As in other reconsolidation studies from this group, alcohol-associated memories were retrieved by presenting abstinent participants with a glass of beer and then taking it away unexpectedly before the first sip [ 29 , 54 , 74 , 76 ].…”
Section: Alcoholmentioning
confidence: 99%
“…Immediately after memory retrieval, alcohol cues were re-associated with gustatory disgust, leading to subsequent reduction in alcohol cue valuation, attentional capture, and alcohol craving [ 54 , 74 ]. Moreover, the same group showed that disgust-based counterconditioning of drinking cues conducted following memory retrieval led to greater long-term reductions in drinking (9 months) in hazardous drinkers [ 75 ]. These findings suggest that the retrieval-counterconditioning manipulation leads to integration of the new information into the memory, by “rewriting” the valence of alcohol cues in humans.…”
Section: Alcoholmentioning
confidence: 99%
“…To begin the drug-related memory reconsolidation process, patients could be presented with drug cues that make them mentally travel back in time and retrieve the emotional experiences for further elaboration. Previously conducted trials that implemented behavioral memory reconsolidation interventions were often supplemented by extinction-enhancing pharmacological treatments such as D-cycloserine (10)(11)(12) or βadrenergic antagonists like Propranolol (13,14) and have shown to be impactful in terms of drug cue reactivity extinction (15)(16)(17). Positive results in the extinction of drug cue reactivity are suggested to be highly dependent on the efficiency of reactivating maladaptive drug memories (18,19), and that comes as no surprise that drug cue-exposure seems like a promising strategy for aiding retrieval and reactivation of such memories.…”
Section: Memory Reconsolidation and Cue Exposurementioning
confidence: 99%